Rum runners - Nelson, William (Motion picture producer and director); Bright, Yves; Boyd, Brian Stuart; Wells, Vernon, 1945- (ITD Productions, 2016)
Rum Runners is the epic story of two best friends, Vic Hanson and Don Calyer. They get caught running illegal booze across the Canadian border. This outstanding screenplay is inspired by actual events. --